DEFFERED TAX EXPENSE, PROFITABILITY, DISCRETIONARY ACCRUALS DAN MANAJEMEN LABA - Husna Khalida; M. Irfan Tarmizi (JABE (Journal of Applied Business and Economic), 2015)
This research examines the effect of deffered tax expense and profitability on earning management with discretionary accruals as interverning variable. The purpose of this study was to determine the effect of deffered tax expense and discretionary accruals on earning management proxied by return on assets with deffered tax expense proxied by discretionary accruals as variable that mediated the connection between deffered tax expense with earning management. The population in this research are all chemical manufacturing companies listed in Indonesia stock exchange during the period 2009-2013 using sampling methods that non-probability: purposive sampling. Based on predetermined criteria, there are 14 companies during years 2009 – 2013 were used as a sample with 70 observations during the time of observation. The results show that:  (1) deffered tax expense does not affect the discretionary accruals;(2) deffered tax expense doesn’t have significant positive effect on earning management;(3) discretionary accruals doesn’t have significant positive effect on earning management;(4) profitability has positive effect on earning management;and (5) discretionary accruals as an interverning variable that mediates the effect of deffered tax expense on earning management. Based on agency theory in outline, earning management is affected by the conflict of interest between agents and principal that arise when a part seeks to achieve or maintain a level of prosperity and motivated to improve himself with ever-increasing profitability proved by significant influence between Return On Asset as profitability variables on earnings management and also given that the accrual policy is a way of earning management manager and deffered Tax Expense reflects the accrual policies with different amount of time that is generated, then the Tax Expense deffered is used as a measure in detecting earnings management in research Here you are. So deffered tax expense through discretionary accruals that can affect their earnings management.